Hydrogen Cyanamide Causes Reversible G2/M Cell Cycle Arrest Accompanied by Oxidation of the Nucleus and Cytosol - Yazhini Velappan; Ambra de Simone; Santiago Signorelli; John A. Considine; Christine H. Foyer; Michael J. Considine (Antioxidants, 2023)
Hydrogen cyanamide (HC) has been widely used in horticulture to trigger bud burst following dormancy. Its use has been banned in some countries due to human health concerns, however the search for effective safe alternatives is delayed by lack of knowledge of the mechanism of HC action. Earlier studies demonstrate that HC stimulates the production of reactive oxygen species (ROS) and alters the rate of cell division. However, the relationships between HC effects on ROS, redox (reduction/oxidation) homeostasis and cell division are unknown. This study used Arabidopsis thaliana ((L.) Heynh.) seedlings expressing the redox reporter roGFP2 to measure the oxidation states of the nuclei and cytosol in response to HC treatment. The Cytrap dual cell cycle phase marker system and flow cytometry were used to study associated changes in cell proliferation. HC (1.5 mM) reversibly inhibited root growth during a 24 h treatment. Higher concentrations were not reversible. HC did not synchronise the cell cycle, in contrast to hydroxyurea. Rather, HC caused a gradual accumulation of cells in the G2/M phase and decline of G1/S phase cells, 16 to 24 h post-treatment. This was accompanied by increased oxidation of both the nuclei and cytosol. Taken together, these findings show that HC impairs proliferation of embryonic root meristem cells in a reversible manner through restriction of G2/M transition accompanied by increased cellular oxidation.